A review of the historical and current relationship between positive behaviour support and applied behaviour analysis: impact and future directions. Issue 2 (3rd July 2022) - Fernández-Mateos, Jose M.; Conlon, Niall J.; Murray, Clodagh M.; Healy, Olive
ABSTRACT: When providing support for people with intellectual or developmental disabilities (IDD), it is important that evidence-based strategies are utilised in an ethical manner with the wellbeing of the individuals supported at the centre of all decision-making. Proponents of Applied Behaviour Analysis (ABA) and Positive Behaviour Support (PBS) have been known to engage in discussions that can be polarising, and the overlap between the two disciplines is not always clear. The current paper reviews the literature around the sometimes-strained relationship between PBS and ABA over the past 40 years, with a view to understanding the current position and discourse. Arising from this, we outline ways in which this current position may result in negative outcomes for the people supported, individuals in need of support and their families. The aim of this paper is to create a starting point to discuss how we can work together to create better outcomes for all.